1993
DOI: 10.2165/00002018-199309060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Chemotherapy-Induced Nausea and Vomiting Current Perspectives and Future Possibilities

Abstract: Nausea and vomiting are among the most distressing adverse effects of cancer chemotherapy. In the last 10 years considerable advances in the prevention of chemotherapy-induced emesis have been made. From an analysis of the results obtained in patients receiving moderately- to severely-emetogenic drugs the following guidelines in choosing the best antiemetic treatment can be given: 1. For the prevention of acute emesis induced by a high single dose of cisplatin (> or = 50 mg/m2) or by low doses (20 to 40 mg/m2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 87 publications
1
17
0
2
Order By: Relevance
“…As in previous dolasetron studies [14,15,23,30,31] and other 5-HT 3 antagonists trials [32,33], tiredness and headache were the most commonly reported adverse events. As in previous studies with 5-HT 3 receptor antagonists [3,13,15,22,23,31,32,34], we also noted asymptomatic changes in ECG intervals. None was of clinical consequence or required medical treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As in previous dolasetron studies [14,15,23,30,31] and other 5-HT 3 antagonists trials [32,33], tiredness and headache were the most commonly reported adverse events. As in previous studies with 5-HT 3 receptor antagonists [3,13,15,22,23,31,32,34], we also noted asymptomatic changes in ECG intervals. None was of clinical consequence or required medical treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Until recently, the dopamine receptor antagonist metoclopramide was considered the cornerstone of antiemetic treatment. It confers antiemetic protection at high doses [3] but is associated with extrapyramidal side effects, especially in children, adolescents, and young adults [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the chemical structures of all drugs in this class are similar, the individual 5-HT 3 -receptor antagonists exhibit notable pharmacologic differences in their selectivity, potency, dose-response profiles, and half-lives [1,40,41] that may affect their activities as antiemetic agents in certain individuals. For example, pharmacologic potencies of these agents differ; the rank order of the U.S.-licensed agents is granisetron > ondansetron > dolasetron.…”
Section: A Comparable Pharmacologic Profile?mentioning
confidence: 99%
“…Delayed emesis represents a significant problem and may contribute to poor overall emetic control, as well as to the possible development of anticipatory nausea and vomiting in subsequent chemotherapy cycles [93]. Although NK 1 receptors and substance P, believed to be essential components of the emetic response, have been shown to be involved in the induction of delayed emesis [94, 95], the mechanism underlying delayed symptoms is less well understood than that of acute-onset emesis.…”
Section: -Ht3-receptor Antagonists In Delayed Emesismentioning
confidence: 99%